Islam, law and identity - Diamantides, Marinos ca. 21. Jh.; Gearey, Adam (Routledge, 2012)
Islam, Law and Identity brings together a range of Muslim and non Muslim scholars in order to focus on recent debates about the nature of sacred and secular law